DIFFERENTIAL HEATS OF ORTA-XYLENE IN ZEOLITE AgZSM-5 (E Global Congress, 2023)
This paper presents the differential heat of adsorption of o-xylene on zeolite AgZSM-5 at a temperature of 303 K, obtained by the microcalorimetric method. A correlation between the adsorption-energy characteristics was found and the molecular mechanism of o-xylene adsorption in AgZSM-5 zeolite was revealed in the entire filling region. A stepwise nature of the heat of adsorption of o-xylene was revealed. The adsorption of the o-xylene molecule forms by the intersection of straight and zigzag channels and the formation of ion/molecular complexes of various multiplicity in them.